Two distinct resident macrophage populations coexist in the ovary - Li, Nianyu; Li, Zhuqing; Fang, Fang; Zhu, Chendi; Zhang, Wenzhe; Lu, Yueshuang; Zhang, Rongrong; Si, Pinxin; Bian, Yuehong; Qin, Yingying; Jiao, Xue (Frontiers in Immunology, 2022)
Tissue-resident macrophages (TRMs) are highly heterogeneous and have a complex and important role in tissue support, homeostasis, and function. The heterogeneity, maintenance, and function of TRMs, as one of the major immune cells in the ovary, are not well understood. Here, we described two distinct macrophage subsets, F4/80hiCD11bint and F4/80intCD11bhi, with different phenotypic characteristics in the ovary in mice. The F4/80hiCD11bint population contained a distinct CD206+ subgroup and highly expressed CD81, while the F4/80intCD11bhi subset showed higher expression of CCR2 and TLR2. Notably, Ly6c+ macrophages were present almost exclusively in the F4/80intCD11bhi subpopulation. Combining in vivo fate mapping and parabiotic mouse models, we characterized the longevity and replenishment of the two macrophage populations. We found that both the F4/80hiCD11bint and F4/80intCD11bhi subsets were ovary-resident. Importantly, the F4/80hiCD11bint macrophages acted as a self-maintaining and long-lived population with a modest monocyte contribution at a steady state, and the F4/80intCD11bhi subpopulation had a relatively short lifespan with a greater contribution from monocytes. After macrophage ablation, disturbance of estrogen secretion and ovarian hemorrhage due to damaged vascular integrity was observed in mice. Our data provide critical insights into ovarian macrophage heterogeneity and highlight the strategic role of TRMs in ovarian homeostasis and physiology.